Analysing the antidepressant and drug efflux competence of Clitoria ternatea L. as P-glycoprotein inhibitor to facilitate blood brain barrier - Margret, Arockiya Anita; Dhayabaran, Violet; Suvaithenamudhan, Suvaiarasan; Parthasarathy, Subbiah (Acta Scientiarum. Biological Sciences, 2019)
Clitoria ternatea L. is a vital ayurvedic herb featured with a wide spectrum of mental health benefits. The present study investigates the competence of the plant against depression and to inhibit the membrane efflux protein P-glycoprotein (P-gp) that can regulate and restrict drug permeation into the brain. Antidepressant competence of the aqueous plant extract was assessed by animal despair studies on depression induced female mice models. The P-glycoprotein inhibitory potential of active phytocompounds was evaluated by molecular docking assay and substantiated by a cell line study. The in vivo studies exhibited a significant difference in the immobility time thereby establishing antidepressant activity. The histopathological sections from cortex region of treated brain showed decreased degenerative changes. Ten imperative phytocompounds facilitated docking complexes against P-glycoprotein among which Kaempferol 3-O-(2״,6״-di-O-rhamnopyranosyl) glucopyranoside exhibited a finest docking score of -12.569 kcal mol-1. Conversely it was attested by the rhodamine transport assay that demonstrated the inhibitory potential to surpass blood brain barrier. The outcome of the study endorses the efficacy of Clitoria ternatea L. as an idyllic brain drug and facilitates brain permeability